2013
DOI: 10.1001/jamainternmed.2013.8412
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Screening of the General Population and Long-term Survival

Abstract: dentification of structural heart disease in asymptomatic individuals could allow early disease-modifying treatment. Echocardiography is frequently used to evaluate low-risk individuals, and there is an increasing interest in cardiovascular screening because of public awareness of unexplained cardiac deaths among adults and athletes. 1-3 Because of the low prevalence of structural heart disease among the general population, echocardiography has traditionally not been considered justified in low-risk individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 26 publications
0
41
3
Order By: Relevance
“…Unrestricted population screening using echocardiography is not an answer since it has a low yield 3 and is therefore more likely to cause anxiety 4,5 than find clinically significant abnormalities. However it has been suggested 6,7 that echocardiography should be more readily available for patients with a high likelihood of cardiac disease based on history, signs or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Unrestricted population screening using echocardiography is not an answer since it has a low yield 3 and is therefore more likely to cause anxiety 4,5 than find clinically significant abnormalities. However it has been suggested 6,7 that echocardiography should be more readily available for patients with a high likelihood of cardiac disease based on history, signs or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial [19], ultrasound screening for AAA was found to be not effective in men aged 65-83 years and did not reduce overall death rates. Another study [20] showed that echocardiographic screening for structural and valvular heart disease in the general population provided no benefit for mortality or for the risk of myocardial infarction or stroke. The reasons for the contrary outcomes between those studies remain unclear; however, some potential underlying reasons might exist.…”
Section: Effect Of Cad Screening On Mortalitymentioning
confidence: 99%
“…Disease should not be defined or managed by measurements and ratios in isolation [23,26,27]. The pervasive use of population based associations, absence of uniform screening methodology, and the lack of a unified solution to a social imperative deserves a critical review.…”
Section: Something Overlookedmentioning
confidence: 99%
“…Most testing modalities entrenched in consensus guidelines [68] are not capable of identifying nearterm risk(occurring within 1 year of assessment), but classify risk over many years (10 years for the Framingham Risk Score) [69,70]. Most clinical tests are currently known to be of little or no benefit in asymptomatic persons [26] and include: physical exam [42], resting and stress ECG [2,37,39,40,42,43], complete, limited and/or screening echo cardiographic exam [2,18,26,71], various imaging modalities such as MRI [37], CT calcium score [37], and serum biomarkers [72][73][74], lipid profile [75] and genomic testing [75][76][77].…”
Section: Guidelinesmentioning
confidence: 99%